363 Human Leukocyte Antigen Typing in a Profoundly Leukopenic Patient Refractory to Platelet Transfusions. (11th January 2018) - Booth, Adam; Vaidya, Smita; Bryant, Barbara
Abstract: Introduction: Platelet refractoriness is a common problem leading to delays in treatment, increased length of hospital stay, and higher inpatient costs. A 39-year-old woman with a past medical history of insulin-dependent diabetes and hypothyroidism presented with malaise, non-healing mouth ulcer, gum bleeding, hematochezia, and left axillary abscess. She was diagnosed with precursor B-cell acute lymphocytic leukemia. Due to severe thrombocytopenia and need for chemotherapy optimization, the patient received multiple platelet transfusions during her hospitalization. She became refractory, ABO-compatible platelets were transfused without success, and human leukocyte antigen (HLA) antibody testing revealed 65 antibodies. HLA antigen typing was attempted, but the patient's white blood cell count was too low to obtain results, and buccal testing was not available at the institution. Neurosurgery planned for an Ommaya reservoir placement for intrathecal chemotherapy' however, the procedure was delayed due to severe thrombocytopenia (2, 000/uL). Methods: We contacted the patient's biological sisters and coordinated efforts to have specimens drawn and sent to our institution for HLA typing. The patient's mother had samples drawn on site for genotyping. The patient's father was estranged. Results from genotyping the patient's mother and two sisters allowed us to determine the patient's most probable HLA genotype. Conclusion: We worked closely with our blood centers to obtain HLA-matched platelets with a combination of compatible and least incompatible haplotypes. Neurosurgery required a platelet count of 50, 000/uL to perform the procedure. Following the second apheresis unit, the platelet count improved to 54, 000/uL with a corrected count increment of 15, 600. This case presented a refractory thrombocytopenic patient with antibodies to nearly all HLA antigens, who required an invasive life-saving procedure, and whom we were unable to HLA genotype. Resourcefulness and teamwork facilitated the successful resolution of this challenging clinical problem allowing the patient to have a shorter hospital stay and improved clinical outcome.